Enhanced anti-tumor immunotherapy by dissolving microneedle patch loaded ovalbumin - Lee, Sung-Ju (PLoS One, 2019)
The skin is a very suitable organ for the induction of immune responses to vaccine antigens. Antigen delivery systems to the skin by needle and syringe directly deposit the antigen into the epidermal-dermal compartment, one of the most immunocompetent sites due to the presence of professional antigen-presenting cells aimed at the induction of antigen-specific T cells. In this study, we analyzed the amount of ovalbumin as an antigen delivered to the skin by a microneedle. When ovalbumin protein as an antigen was delivered to the skin of mice using a dissolving microneedle, it induced an immune response through the enhanced proliferation and cytokines production by the splenocytes and lymph nodes. Also, it effectively increased the ovalbumin-specific CD8(+) T cell and CD4(+) T cell population and induced an ovalbumin-specific CTL response against the graft of ovalbumin-expressing EG7 tumor cells in the immunized mice. Also, we identified the inhibition of tumor growth and prevention of tumor formation in the context of the therapeutic and prophylactic vaccine, respectively through EG-7 tumor mouse model. Finally, these data show the potential of patches as attractive antigen delivery vehicles.